2018
DOI: 10.19044/esj.2018.v14n15p12
|View full text |Cite
|
Sign up to set email alerts
|

Bone Transport of Tibia

Abstract: This is a comparative study to evaluate the outcome of forty patients with bone loss in tibia using conventional external fixation device for group A while for group B using Ilizarov external fixator device each group consists of 20 patients, based on principles of distractive osteogenesis. Patients and methods: Forty patients with bone loss of 4 to 14 centimeters in tibia between April 2011 and April 2016 were treated, ages (15-65 years); female to male ratio was 6:34. The cause of defects in tibia was fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…In studies conducted by Elgazzar AS et al in 2012, Rohilla R et al in 2016 and Barawi OA et al 2018 knee stiffness was present in 8%,20% and 10% of cases respectively. Our studies showed decrease in incidence of knee stiffness and ankle stiffness [25,3,28] . Thus we conclude that though we have encountered complications of ilizarov ring fixator but most of the complications are avoidable or can be decreased by diligent postoperative care and physiotherapy.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…In studies conducted by Elgazzar AS et al in 2012, Rohilla R et al in 2016 and Barawi OA et al 2018 knee stiffness was present in 8%,20% and 10% of cases respectively. Our studies showed decrease in incidence of knee stiffness and ankle stiffness [25,3,28] . Thus we conclude that though we have encountered complications of ilizarov ring fixator but most of the complications are avoidable or can be decreased by diligent postoperative care and physiotherapy.…”
Section: Discussionsupporting
confidence: 60%
“…In present study limb length discrepancy was absent in all cases. In studies conducted on ilizarov fixator by Farmanullah et al better than the above studies [27,3,28] . Post operative pain is a major complication of ilizarov fixator.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations